The psychological impact of genocide on the Yazidis - Kizilhan, Jan Ilhan; Berger, Thomas; Sennhauser, Laura; Wenzel, Thomas (Frontiers in Psychology, 2023)
Background: The genocide against the Yazidis by the Islamic State of Iraq and Al-Sham (ISIS) in the Sinjar area of Northern Iraq has costed many lives and has also caused a psychological long-term impact in this minority. This impact can be seen among individual survivors. Additionally, there is a large number of direct and indirect victims and for this reason, the impact can also be observed on the level of the group and society in this region at large. Methodology: The research examines three different population groups (Yazidis members who had been exposed to violence by terrorist group actions, those not exposed to this experience as they were living in an area not directly exposed to ISIS violence, and a control group of non – Yazidi general population members). In total, 425 participants (age range 15-78) took part in the study and participated in interviews using standard scales to measure general physical and mental health. Results: The results demonstrate that psychological stress and suicidality are higher among the Yazidis survivors of violence than in the other Yazidi participants. Conclusions: Psychological Disorders after a genocide and war in post-conflict populations should receive more attention in the planning of mental health care and prevention and should be seen as a major problem, especially in camp settings and displaced persons besides the usual increased prevalence of posttraumatic stress and other disorders covered by research so far in this context.